Plasma Metabolites and Gut Microbiota Are Associated With T cell Imbalance in BALB/c Model of Eosinophilic Asthma - Zhou, Yumei; Wang, Tieshan; Zhao, Xiaoshan; Wang, Ji; Wang, Qi (Frontiers in Pharmacology, 2022)
The pathogenesis of allergic asthma is complex, it is usually caused by immune system imbalance. Th1, Th2, regulatory T cells (Treg) and T helper 17 (Th17) cells have an important role in the pathogenesis of eosinophilic asthma. Yet, the exact role of Th1, Th2, Treg and Th17 cells in eosinophilic asthmatic disease is not fully understood. This study used an untargeted plasma metabolomics combine 16S rDNA technology to identify new biomarkers of plasma metabolites and gut microbiota in ovalbumin-induced eosinophilic allergic asthma in BALB/c mice to further explore the biomarkers in regulating the immune balance or the immune response. We discovered that malate, l-dihydroorotate were associated with Th1/Th2 and Treg/Th17 cells balance, imidazoleacetic acid was associated with Th1/Th2 cell balance, 1,5-anhydro-d-sorbitol was associated with Treg/Th17 cell balance. The results also found that genus Candidatus Arthromitus of gut microbiota were associated with Th1/2, Treg/Th17 balance, genus Ruminiclostridium 6, they were all associated with Th1/2 and Treg/Th17 cell balance, while the gut microbiota were not associated with penh value which reflect airway hyperresponsiveness (AHR) in the eosinophilic asthma mice model. Interestingly, the plasma metabolite biomarkers of malate, l-dihydroorotate are associated with genus Ruminiclostridium 6, they were all associated with Th1/2 and Treg/Th17 cell balance, while imidazoleacetic acid is associated with genus Ruminiclostridium 6 which is associated with Th1/2 balance. Among the differential plasma metabolites, 1,5-anhydro-d-sorbitol is associated with genus Ruminiclostridium 6 and genus Candidatus Arthromitus. Among them, malate participate in the T cell activation, T cell differentiation and activation may be a new research direction in eosinophilic allergic asthma. We firstly study the gut microbiota and plasma metabolites markers of immune balance in eosinophilic asthma in mice model, laying a foundation for drug treatment in eosinophilic allergic asthma.